Social inclusion: a platform for social integration in Cosmo City - Jayawardena, Chayneeka (My University, 2012)
The thesis ,aims to explore, how architecture and urban design as a tool can create an inclusive environment that allows diverse people to gather and socialise. And in addition question how principles of movement, access, multi- use and open space can create a design that becomes responsive to its context and users. The research Context for the thesis is based in Cosmo City. Cosmo City is described as a mixed use inclusionary housing development that was designed to integrate families from different income groups. The development has replicated the forms of an apartheid township. Which has no attempt to create an urban development that encompassed qualities of inclusivity and integration. But in contrast the impression was that of exclusion and isolation. Through mapping, photographs and sketches I was able to illustrate inclusive and exclusive spaces, informal activity and formal facilities of Cosmo City which gave more insight into understanding the context from all perspectives. Through an in-depth analysis of the context and a workshop with residents. I was able to develop a programme for a Sports Centre facility that aims to provide a platform for social inclusion and development in Cosmo City. The aim of the design intervention is to create a space that accommodates all users and various types of activity that can bring people together. The design intervention should allow for access to facilities and resources while providing a framework for informal and formal activity to take place freely. The intervention ultimately sets the pre-conditions to allow for inclusive activity and integration to take place in Cosmo City.